Functions and Symbolism of Staffage in the Landscape Canvas Space in Russia of the Second Half of the 18th Century - Karev, Andrey A. (Actual Problems of Theory and History of Art, 2023)
The article discusses the role and place of staffage in the illusory space of an easel painting in interaction with a complex of problems related in one way or another to the landscape. The question has never been previously posed this way, since staffage in the history of art is usually perceived as sometimes necessary, but invariably secondary addition to the genre or “kind” of painting, which in the 18th century was called “landscape”. Since in Russia one of the most important branches of landscape, associated primarily with the work of Semyon Shchedrin, is an image of park space, it seems promising to address the patterns of arrangement of this space together with the rules of conduct for the owners of the estate and their guests, which are reflected in the picturesque version. Such an approach also takes into account the creative experience of Russian painters in the style of the ideal Italian landscape. An example of a specific variation of the manor staffage can be seen in the canvases of I. M. Tankov. The grotesqueness characteristic of the work of this master in the interpretation of the image of the Russian peasant becomes more obvious in rural landscapes dedicated to holidays. On the whole, in the existing variants of the landscape, in its entirety, the question of micro-macrocosmic correlations arises, connected with the theme of “man and nature”, the interest to which intensified at the end of the 18th century. Under these conditions, the tradition arises of viewers mentally joining the depicted staffage in order to unanimously open their hearts, in accordance with the ideas of sentimentalists, to natural beauties. The identification of the resonance of a number of literary and pictorial motifs in the staffing variations made it possible to single out the pastoral and the sentimental journey among the most important themes of landscape painting. There is every reason to believe that in the practice of interacting with the viewer, landscape masters actively use the emblematic and symbolic potential of staffage, which contributes to the creation of a dense allegorical atmosphere worthy of a historical picture.